Tangent of f(x)

If f(cos(2x))=sec2(x)2sin2(x)+1 f(\cos(2x)) = \sec^2 (x) - 2\sin^2 (x) + 1 , find the rate of change of y=f(x)y=f(x) when x=12x =\frac12.

#Calculus

Note by Majed Musleh
6 years ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Using the identity cos(2x)=2cos2(x)1cos2(x)=12(1+cos(2x))\cos(2x) = 2\cos^{2}(x) - 1 \Longrightarrow \cos^{2}(x) = \dfrac{1}{2}(1 + \cos(2x)) we have that

f(cos(2x))=1cos2(x)2(1cos2(x))+1=21+cos(2x)2+(1+cos(2x))+1=21+cos(2x)+cos(2x).f(\cos(2x)) = \dfrac{1}{\cos^{2}(x)} - 2(1 - \cos^{2}(x)) + 1 = \dfrac{2}{1 + \cos(2x)} - 2 + (1 + \cos(2x)) + 1 = \dfrac{2}{1 + \cos(2x)} + \cos(2x).

Letting v=cos(2x)v = \cos(2x) we can write the function as f(v)=21+v+v,f(v) = \dfrac{2}{1 + v} + v, and since vv can now just be considered a "dummy" variable we can re-label it as xx to end up with the function in the form f(x)=21+x+x.f(x) = \dfrac{2}{1 + x} + x.

Now f(x)=2(1+x)2+1,f'(x) = -\dfrac{2}{(1 + x)^{2}} + 1, and so f(12)=294+1=19.f'(\frac{1}{2}) = -\dfrac{2}{\frac{9}{4}} + 1 = \dfrac{1}{9}.

Brian Charlesworth - 6 years ago
×

Problem Loading...

Note Loading...

Set Loading...